Global estimates on the number of people blind or visually impaired by cataract: a meta-analysis from 2000 to 2020 - Pesudovs, Konrad; Jonas, Jost B. (Eye, 2024)
To estimate global and regional trends from 2000 to 2020 of the number of persons visually impaired by cataract and their proportion of the total number of vision-impaired individuals.
Gesehen am 31.03.2025
Mitglieder der Vision Loss Expert Group of the Global Burden of Disease Study and GBD 2019 Blindness and Vision Impairment Collaborators: Konrad Pesudovs, Van Charles Lansingh, John H. Kempen, Ian Tapply, Arthur G. Fernandes, Maria Vittoria Cicinelli, Alessandro Arrigo, Nicolas Leveziel, Serge Resnikoff, Hugh R. Taylor, Tabassom Sedighi, Seth Flaxman, Mukkharram M. Bikbov, Tasanee Braithwaite, Alain Bron, Ching-Yu Cheng, Monte A. Del Monte, Joshua R. Ehrlich, Leon B. Ellwein, David Friedman, João M. Furtado, Gus Gazzard, Ronnie George, M. Elizabeth Hartnett, Jost B. Jonas, Rim Kahloun, Moncef Khairallah, Rohit C. Khanna, Janet Leasher, Julie-Anne Little, Vinay Nangia, Michal Nowak, Tunde Peto, Pradeep Ramulu, Fotis Topouzis, Mitiadis Tsilimbaris, Ya Xing Wang, Ningli Wang, Rupert Bourne, Konrad Pesudovs, Van Charles Lansingh, John H. Kempen, Ian Tapply, Arthur G. Fernandes, Maria Vittoria Cicinelli, Alessandro Arrigo, Nicolas Leveziel, Paul Svitil Briant, Theo Vos, Serge Resnikoff, Seth Flaxman, Yohannes Habtegiorgis Abate, Mohammad Abdollahi, Mozhan Abdollahi, Ayele Mamo Abebe, Olumide Abiodun, Richard Gyan Aboagye, Woldu Aberhe Abrha, Hasan Abualruz, Hiwa Abubaker Ali, Eman Abu-Gharbieh, Salahdein Aburuz, Tadele Girum Girum Adal, Mesafint Molla Adane, Isaac Yeboah Addo, Qorinah Estiningtyas Sakilah Adnani, Muhammad Sohail Afzal, Shahin Aghamiri, Bright Opoku Ahinkorah, Aqeel Ahmad, Sajjad Ahmad, Ali Ahmadi, Ayman Ahmed, Haroon Ahmed, Ahmad Samir Alfaar, Abid Ali, Syed Shujait Shujait Ali, Awais Altaf, Hubert Amu, Sofia Androudi, Rodrigo Anguita, Abhishek Anil, Saeid Anvari, Anayochukwu Edward Anyasodor, Francis Appiah, Jalal Arabloo, Mosab Arafat, Damelash Areda, Reza Arefnezhad, Brhane Berhe Aregawi, Akeza Awealom Asgedom, Tahira Ashraf, Seyyed Shamsadin Athari, Bantalem Tilaye Tilaye Atinafu, Maha Moh’d Wahbi Atout, Alok Atreya, Haleh Ayatollahi, Ahmed Y. Azzam, Hassan Babamohamadi, Sara Bagherieh, Yogesh Bahurupi, Atif Amin Baig, Biswajit Banik, Mainak Bardhan, Saurav Basu, Kavita Batra, Nebiyou Simegnew Bayileyegn, Fatemeh Bazvand, Addisu Shunu Beyene, Devidas S. Bhagat, Akshaya Srikanth Bhagavathula, Pankaj Bhardwaj, Sonu Bhaskar, Jasvinder Singh Bhatti, Mukharram Bikbov, Niloufar Bineshfar, Marina G. Birck, Veera R. Bitra, Tasanee Braithwaite, Katrin Burkart, Yasser Bustanji, Zahid A. Butt, Florentino Luciano Caetano dos Santos, Luis Alberto Cámera, Vera L.A. Carneiro, Muthia Cenderadewi, Eeshwar K. Chandrasekar, Vijay Kumar Chattu, Nitin Chitranshi, Hitesh Chopra, Dinh-Toi Chu, Kaleb Coberly, João M. Coelho, Natália Cruz-Martins, Omid Dadras, Xiaochen Dai, Subasish Das, Ana Maria Dascalu, Mohsen Dashti, Maedeh Dastmardi, Berecha Hundessa Demessa, Biniyam Demisse, Diriba Dereje, Awoke Masrie Asrat Derese, Nikolaos Dervenis, Vinoth Gnana Chellaiyan Devanbu, Thanh Chi Do, Thao Huynh Phuong Do, Francisco Winter dos Santos Figueiredo, Arkadiusz Marian Dziedzic, Hisham Atan Edinur, Ferry Efendi, Joshua R. Ehrlich, Michael Ekholuenetale, Temitope Cyrus Ekundayo, Iman El Sayed, Muhammed Elhadi, Mohammad Hassan Emamian, Mehdi Emamverdi, Azin Etemadimanesh, Adeniyi Francis Fagbamigbe, Ayesha Fahim, Hossein Farrokhpour, Ali Fatehizadeh, Alireza Feizkhah, Lorenzo Ferro Desideri, Getahun Fetensa, Florian Fischer, Ali Forouhari, Matteo Foschi, Kayode Raphael Fowobaje, Abhay Motiramji Gaidhane, Aravind P. Gandhi, Miglas W.W. Gebregergis, Mesfin Gebrehiwot, Brhane Gebremariam, Urge Gerema, Fariba Ghassemi, Sherief Ghozy, Mahaveer Golechha, Pouya Goleij, Bárbara Niegia Garcia Goulart, Shi-Yang Guan, Zewdie Gudisa, Sapna Gupta, Veer Bala Gupta, Vivek Kumar Gupta, Arvin Haj-Mirzaian, Aram Halimi, Shahin Hallaj, Samer Hamidi, Mehdi Harorani, Hamidreza Hasani, Demisu Zenbaba Heyi, Nguyen Quoc Hoan, Ramesh Holla, Sung Hwi Hong, Mehdi Hosseinzadeh, Chengxi Hu, John J. Huang, Hong-Han Huynh, Segun Emmanuel Ibitoye, Irena M. Ilic, Mustapha Immurana, Md. Rabiul Islam, Sheikh Mohammed Shariful Islam, Chidozie C.D. Iwu, Louis Jacob, Ammar Abdulrahman Jairoun, Manthan Dilipkumar Janodia, Shubha Jayaram, Har Ashish Jindal, Mohammad Jokar, Nitin Joseph, Charity Ehimwenma Joshua, Vidya Kadashetti, Laleh R. Kalankesh, Rohollah Kalhor, Sagarika Kamath, Himal Kandel, Rami S. Kantar, Ibraheem M. Karaye, Hengameh Kasraei, Soujanya Kaup, Navjot Kaur, Rimple Jeet Kaur, Gbenga A. Kayode, Yousef Saleh Khader, Himanshu Khajuria, Rovshan Khalilov, Mahalaqua Nazli Khatib, Adnan Kisa, Soewarta Kosen, Ai Koyanagi, Kewal Krishan, Mukhtar Kulimbet, Nithin Kumar, Om P. Kurmi, Chandrakant Lahariya, Tuo Lan, Iván Landires, Janet L. Leasher, Munjae Lee, Seung Won Lee, Wei-Chen Lee, Stephen S. Lim, Julie-Anne Little, Preetam Bhalchandra Mahajan, Sandeep B. Maharaj, Alireza Mahmoudi, Razzagh Mahmoudi, Kashish Malhotra, Tauqeer Hussain Mallhi, Vahid Mansouri, Emmanuel Manu, Roy Rillera Marzo, Andrea Maugeri, Colm McAlinden, Wondwosen Mebratu, Tesfahun Mekene Meto, Yang Meng, Abera M. Mersha, Tomislav Mestrovic, Le Huu Nhat Minh, Awoke Misganaw, Manish Mishra, Sanjeev Misra, Nouh Saad Mohamed, Soheil Mohammadi, Mustapha Mohammed, Hoda Mojiri-forushani, Ali H. Mokdad, Hossein Molavi Vardanjani, Mohammad Ali Moni, Fateme Montazeri, Maryam Moradi, Rohith Motappa, Parsa Mousavi, Admir Mulita, Christopher J.L. Murray, Ganesh R. Naik, Gurudatta Naik, Shumaila Nargus, Zuhair S. Natto, Biswa Prakash Nayak, Mohammad Negaresh, Hadush Negash, Dang H. Nguyen, Phat Tuan Nguyen, Van Thanh Nguyen, Robina Khan Niazi, Osaretin Christabel Okonji, Andrew T. Olagunju, Matthew Idowu Olatubi, Michal Ordak, Uchechukwu Levi Osuagwu, Nikita Otstavnov, Mayowa O. Owolabi, Vision Loss Expert Group of the Global Burden of Disease Study, GBD 2019 Blindness and Vision Impairment Collaborators